\(\sqrt{24+8\sqrt{9-x^2}}=x+2\sqrt{3-x}+4\) \(\left(Đk:-3\le x\le3\right)\)
\(\sqrt{4\left(x+3\right)+8\sqrt{9-x^2}+4\left(3-x\right)}=x+2\sqrt{3-x}+4\)
\(\sqrt{\left(2\sqrt{x+3}+2\sqrt{3-x}\right)^2}=x+2\sqrt{3-x}+4\)
\(2\sqrt{x+3}+2\sqrt{3-x}=x+2\sqrt{3-x}+4\)
\(2\sqrt{x+3}=x+4\)
\(4\left(x+3\right)=x^2+8x+14\)
\(x^2+4x+2=0\)
\(\Delta=16-8=8\)
\(\Delta>0\)=> phương trình có 2 nghiệm phân biệt
\(\left[{}\begin{matrix}x=\dfrac{-4+2\sqrt{2}}{2}=-2+\sqrt{2}\\x=\dfrac{-4-2\sqrt{2}}{2}=-2-\sqrt{2}\end{matrix}\right.\)